The Mediterranean Genetic Code Grapevine and Olive - Poljuha, Danijela; Sladonja, Barbara (IntechOpen, 2013)
The book "The Mediterranean Genetic Code - Grapevine and Olive" collects relevant papers documenting the results of research in grapevine and olive genetics, as a contribution to overall compendium of the existing biodiversity for both species with insight into molecular mechanisms responsible for their desirable and important traits. Book encompasses a broad and diverse palette of different topics related to grapevine and olive genetics, with no areal or any other strict limitation, keeping the title as a loose frame for borderless science. Divided in four sections it takes us for a "molecular walk" through different levels of genetic variability, uncovering the remains of still existing wild populations and treasures of neglected local peculiarities, weaving the network from plant to product and back to the beginning, to the hearth of all questions asked and answers hidden in genetics.